Motif Penggunaan Media Sosial Instagram di Kalangan Mahasiswa Ilmu Perpustakaan UIN Sumatera Utara - Kartini, Kartini; Supit, Iyen; Rahimi, Adha; Simatupang, Angraini; Rambe, Rahot Martua (Sci-tech Journal, 2023)
This study aims to identify and analyze cognitive motives and affective motives for using Instagram social media among students of Bibliotechnology, State Islamic University of North Sumatra. This research uses constructivism paradigm with qualitative approach and descriptive procedure. The research subjects were 2 students. Methods of collecting information were tried through interviews, participatory observation, and library research. The information analysis technique was tried with an interactive information analysis model consisting of information reduction, information presentation, and drawing conclusions. The validity of the information is tested through triangulation of sources. The results of the research prove that: 1) The cognitive motives for using Instagram among students prove that there is a fulfillment of data needs from data exchange (sharing) which is the attractive side of Instagram, there is a need to reach the ideational level by sorting content so that what is displayed is perfect imagery and reaches emotional level as an effort to seek attention while fulfilling emotional pleasure. 2) Affective motives for using Instagram social media are directed through the willingness to get new experiences based on other people's content, the willingness to get reactions to the uploaded content, the willingness to acknowledge the image of the account owner so as to urge false reality, and the desire to feel comfortable in the form of a feeling of calm when using Instagram. Keywords: Motif, social media, Instagram, uses and gratification theory.